Religions' Body Perception And The Control Of The Woman Body - Karakaya, Handan (Fırat University, 2021)
The body expresses a whole that is shaped by the effect of different factors in the social whole. The individual is actually subject to a period of formation from the day she/he is born. Attitude, behavior, and gender perception accompany this shaping process, but the body is at the forefront. Societies, religions, cultures, families, traditions desire bodies shaped according to their own norms. In this context, we can say that religions have an important power on the formation of bodies. In this context, we can say that religions have an important power on the formation of bodies. Therefore, it is important that her/his body is shaped by the values of religion and that she adopts appropriate attitudes in terms of expressing the visibility of the idealized religious individual. In this context, in terms of religions, although the bodies are the areas where religious values are processed and gained content, they also carry the process of participation of this idealizedness in life. In this study, the way bodies are perceived by religions and the control processes of women's bodies through these perceptions will be emphasized. Revealing the body perceptions of all religions is a subject that goes beyond the limits of this study. This study was carried out with the data obtained by using literature review and document review techniques.

Beden toplumsal bütün içerisinde farklı faktörlerin etkisiyle biçimlenen bir bütünü ifade etmektedir. Birey dünyaya geldiği günden itibaren aslında bir biçimlendirilme sürecine tabidir. Bu biçimlenme sürecine tutumu, davranış, cinsiyet algısı, eşlik etmekle birlikte, beden en ön sırada durmaktadır. Toplumlar, dinler, kültürler, aileler, gelenekler kendi normlarına göre biçimlenmiş bedenler arzu etmektedirler. Bu bağlamda dinlerin de bedenlerin biçimlenişi üzerinde önemli bir güce sahip olduğunu söyleyebiliriz. Dinler açısından bedenler normlarını pratik ve görünürlük kazandığı alanlardır. Dolayısıyla bedeninin dinin değerleri üzerinden biçim alması, buna uygun tutumlar benimsemesi idealize edilmiş dindar bireyin görünürlüğünü ifade etmesi bağlamında önemlidir. Bu bağlamda dinler açısından bedenler dini değerlerin işlendiği ve içerik kazandığı alanlar olmakla birlikte bu idealize edilmişliğin yaşama katılım sürecini de üzerinde taşımaktadır. Bu çalışmada bedenlerin dinler tarafından algılanış biçimleri ve bu algılanış biçimleri üzerinden de kadın bedenini denetim süreçleri üzerinde durulacaktır. Tüm dinlerin beden algılarını ortaya koymak bu çalışmanın sınırlarını aşan bir konudur. Dolayısıyla dinlerin beden algısı üç kitaplı din üzerinden ele alınacaktır. Bu çalışma kaynak taraması ve doküman incelemesi teknikleri kullanılarak elde edilen verilerle gerçekleştirilmiştir.
DİNLERİN BEDEN ALGISI VE KADIN BEDENİNİN DENETİMİ